1983
DOI: 10.1210/endo-113-1-7
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Phosphatidylinositol Turnover: A Possible Postreceptor Mechanism for the Prolactin Secretion-Inhibiting Effect of Dopamine*

Abstract: We studied the association between the inhibition of phosphatidylinositol (PI) turnover and the inhibition of PRL secretion in the presence of dopamine. The incorporation of radiolabeled phosphate into anterior pituitary gland PI as well as serum PRL levels were significantly (P less than 0.01) greater in female than in male rats. No significant sex-related difference was found in the incorporation by pituitary tissue of 32P into phosphatidylcholine (PC) or phosphatidylethanolamine (PE). Dopamine decreased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(27 citation statements)
references
References 42 publications
0
26
1
Order By: Relevance
“…The receptor-mediated inhibition of PLC as a phenomena was first reported by Canonico et al [12] for the D2 receptor in pituitary and followed up by several groups [13]. Most recently, we also found that the x-opioid agonist inhibited the GTP-stimulated PLC activity in synaptic membranes of the guinea pig cerebellum [14].…”
Section: Introductionmentioning
confidence: 55%
“…The receptor-mediated inhibition of PLC as a phenomena was first reported by Canonico et al [12] for the D2 receptor in pituitary and followed up by several groups [13]. Most recently, we also found that the x-opioid agonist inhibited the GTP-stimulated PLC activity in synaptic membranes of the guinea pig cerebellum [14].…”
Section: Introductionmentioning
confidence: 55%
“…In a number of systems it is well established that activation of D 2 receptor results in multiple signaling mechanisms including inhibition of adenylate cyclase [46][47], inhibition of phosphoinositide turnover [48][49][50], and activation of potassium channels [51]. We further investigated the potential signaling mechanisms involved in the dopamine mediated inhibition of NPY-ir release.…”
Section: Discussionmentioning
confidence: 99%
“…In additional experi ments, the labeling of cellular phospholipids with [3H]-AA was deter mined by incubating the cultured cells for 90 min with [3H]-AA (0.25 gC i/m l) and then extracting and isolating the phospholipids as de scribed previously [8].…”
Section: Incorporation O F Aamentioning
confidence: 99%